Landing limb posture in volleyball athletes with patellar tendinopathy: A pilot study übersetzter Titel (DE) - Kulig, K.; Joiner, D. G.; Chang, Y.-J. (International Journal of Sports Medicine, 2015)
The aims of this pilot study were to investigate how a novel sagittal plane kinematic measurement - the lower extremity contact angle (LECA) - relates to the landing dynamics of elite male volleyball athletes with and without patellar tendinopathy. The LECA was defined as the angle between the ground and the line connecting the center of pressure to the L5S1 marker. 18 athletes (9 with patellar tendinopathy and 9 with asymptomatic tendons) completed simulated spike jumps while instrumented for kinetic and kinematic analysis using a force platform and 3D motion analysis system. The patellar tendinopathic group demonstrated a significantly more acute LECA compared to the asymptomatic group (65.3°±2.2° vs. 69.1°±4.5°) and was the only kinematic or kinetic variable measured to discriminate between the 2 groups. The LECA further demonstrated less variability between trials than sagittal plane hip, knee, and ankle kinematics. Additionally, the LECA`s - and not individual joints` - high correlation with the braking impulse ensures its predictive value for landing dynamics (r=-?0.890). The LECA has the potential to be a valuable tool to help assess jumping athletes in both injury prevention screening and as a variable that, if modified, could help alter the maladaptive behavior observed in symptomatic athletes.